Is it possible to propose a periodization strategy different from the inverted U in preseason? A comparison between two professional football teams - Julen Castellano; David Casamichana; Oier Agirrezabalaga (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Purpose: the main aim of this study was to quantify and compare the weekly external loads of pre-season in two professional football teams. Methods: GPS devices monitored forty-five players in two teams daily in a five-week pre-season period. The external load measures were: number of sessions, total duration, acceleration load (aLoad), total distance (TD), distance at >21 km·h-1 (TD21), distance at >24 km·h-1 (TD24) and Player-Load® (PL). Results: there were differences in the weekly external load between both teams. Team1 trained 30% more time and training sessions than Team2, so the weekly load for all external load variables was higher except for aLoad and TD21 for W1 (Team2>Team1, p<0.05). These differences between teams were not similar for all weeks, with higher differences in weeks 2, 3, and 4. While Team2 proposed a distribution more stable and progressive in high-speed distances (TD21 and TD24) among weeks, Team1 used the inverted U model. In this line, variations between weeks were lower for Team2 (from -4% to 38%) than for Team1 (from -26% to 1,653%). Conclusions: The study's main conclusion was that in addition to a load management with an inverted U model, more widespread in professional football, a more stable and progressive distribution strategy can be proposed in pre-season in a professional setting.